2011
DOI: 10.1016/j.icarus.2011.05.036
|View full text |Cite
|
Sign up to set email alerts
|

Ejecta fragmentation in impacts into gypsum and water ice

Abstract: Please cite this article as: Miljković, K., Mason, N.J., Zarnecki, J.C., Ejecta fragmentation in impacts into gypsum and water ice, Icarus (2011Icarus ( ), doi: 10.1016Icarus ( /j.icarus.2011 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Theoretical and experimental studies [45][46][47] have shown that similar behaviour can be observed for water ice at low temperatures and for rocky materials, suggesting that flash heating might occur on ice 48 . However, quantitative differences between planetary bodies similar to the variability observed between different rocky materials on Earth is expected.…”
Section: Resultsmentioning
confidence: 61%
“…Theoretical and experimental studies [45][46][47] have shown that similar behaviour can be observed for water ice at low temperatures and for rocky materials, suggesting that flash heating might occur on ice 48 . However, quantitative differences between planetary bodies similar to the variability observed between different rocky materials on Earth is expected.…”
Section: Resultsmentioning
confidence: 61%
“…The index α depends on the target material and ranges from 1.5 for loose to 3 for solid targets [ Krivov and Jurewicz , ]. For impacts into pure ice [ Frisch , ; Miljković et al , ] and ice‐silicate mixtures [ Koschny and Grün , ], the value is α = 1.5…1.7, while for impacts into basalt it is α = 2.7 [ Durda and Flynn , ]. Values of α = 1.65…2.37 are consistent with in situ measurements of ejecta from Ganymede [ Krüger et al , ].…”
Section: Correlation Of Fragment Size and Ejection Speedmentioning
confidence: 67%
“…(5)). Single power-law curves are often used for grouped data (Grady, 2009;Miljkovic et al, 2011). For example, the total number of ejecta between 10 mm and 100 mm in size is plotted at the midpoint, 55 mm.…”
Section: Summary Of Cumulative Distributionsmentioning
confidence: 99%